(2-Pyridyl)phenyl methanol: a new reagent for metal-free reduction of nitro aromatic compounds - Giomi, Donatella; Alfini, Renzo; Brandi, Alberto (Tetrahedron, 2011)
As previously reported for 1-(2-pyridyl)-2-propen-1-ol, (2-pyridyl)phenyl methanol is able to react as hydrogen donor towards nitro aromatic and heteroaromatic compounds. Operating in the presence of methyl acrylate as an aza-Michael acceptor, a domino process involving reduction and conjugate addition steps allows the one pot formation of β-amino esters. The crucial role of the pyridine nucleus in making this purely thermal reactivity of carbinols possible has been shown. [Display omitted]